Language and Embodiment - Thang, Nguyen Tat (VNU Journal of Foreign Studies; Vol 25 No 4, 2009)
Abstract. This paper illustrates the relationship between language and embodiment through evidence of the English and Vietnamese language. Evidence presented confirms that there is a close correlation between language and embodiment, thus inferring the implication for the job of teaching and learning languages, which requires the task takers to be equipped with knowledge of this relationship in order to provide a meaningful and productive work .